Pengaruh Stres Kerja dan Lingkungan Kerja Terhadap Tingkat Labour Turnover di CV Hakai Technology Industries Surabaya - Sucianti, Ririn; Mulyati, Awin; Ida Pratiwi, Ni Made (Research Journal of Social Science and Economics, 2025)
This research was conducted at CV Hakai Technology Indutries Surabaya. This company is experiencing a problem, namely a high labor turnover rate, this can be seen in the annual chart which shows an increase in the number of employees leaving, especially in 2022 as many as 25 people leave the company. There are many factors that affect this labor turnover rate , and one of them is work stress and work environment. So this study wants to prove whether work stress factors and work environment affect the high rate of labor turnover in the company. This research is a quantitative research using multiple linear regression analysis, the sample used is a saturated sample, namely all employees at CV Hakai Technology Indutries Surabaya and the data collection technique used is using a closed questionnaire. The results of this study are partially work stress affects labor turnover, partially work environment does not affect labor turnover, and simultaneously work stress and work environment affect high labor turnover at CV Hakai Technology Industries Surabaya